Production of alkaline lipase by Aspergillus terreus AUMC 15762 for laundry application - Osama Abdel-Hafeez Mohamed Al-Bedak; Ahmed Mohamed Ahmed Ali Ramadan; Hussein H. EL-Sheikh; Reda M. Shehata (AMB Express)
Abstract Lipases are extraordinarily critical co-factor-independent enzymes with profound economic consequences. They are utilized extensively in production of fine chemicals, food, textile, pulp and paper, laundry, and biodiesel sectors. In the current study, the lipolytic activity of 141 fungal isolates—representing 21 genera and 38 species—that were isolated from samples of desert soil gathered from the Governorates of Sohag, Qena, and Aswan were examined. Of the 74 isolates showed positive lipase activity, 40 were high lipase producers. In terms of lipase production, Aspergillus terreus AUMC 15762 was the most effective strain. To enhance the synthesis of lipase from Aspergillus terreus AUMC 15762, Plackett–Burman design (PBD) was employed. For the maximal amount of lipase synthesis (103.3 U/mL), ammonium sulphate was required after three days at 25 °C, pH 4.0, and 3.0 g/L. Through the use of Trilite MA 12 anion exchanger and Sephadex G-100 column chromatography, lipase was purified 17.79 times and achieved 64.714 kDa molecular weight on SDS-PAGE. The highest possible specific activity of 3867.85 ± 214.28 U/mg was attained at pH 8.0 and 40 °C. The addition of KCl and ZnSO4 raised the lipase specific activity by 115.42%. Km of 19.0 mg/mL and Vmax of 1000 μmol/min were determined for the pure lipase. The effects of 20 U/mL pure lipase on corn and olive oily spots were examined in this work at pH 8.0 and 40 °C. The pure lipase completely removed oil contamination from fiber surfaces, as evidenced by the oily spots’ separation from the white cotton textiles after 60 min. This work offers a lipase produced from Aspergillus terreus species that showed promise for industrial laundry applications.